Automatização da captação de raios solares para sistemas fotovoltaicos através do mapeamento da trajetória do sol - Silva, Fausto Batista Felix (2019)
Due to the growing demand in the production of electricity in the world, it is necessary to think about alternatives to meet the need for this growth. Currently in several countries, renewable energy sources are being developed, which help to increase energy production and on the other hand collaborate só that these energies are clean, without damaging the environment. One of the alternatives of clean energy is photovoltaic solar energy, which transforms solar energy into electrical energy through photovoltaic modules. The purpose of this work was to develop a solar follower that follows the trajectory of the sun through the mapping of the angle of inclination and solar azimuth in relation to the geographic north, in each season of the year. Also compare its performance in relation to a fixed photovoltaic solar module. The work presents a state of the art showing different types of followers, one and two axes, showing their performances and tracing techniques. Finally, it presents the performance results of the prototype implemented in each season of the year, where data were collected between July 2018 and June 2019, showing the behavior of the solar follower of two axes where the results show a considerable Gain in relation to the fixed photovoltaic module on sunny days reaching an average of 35% in the summer. Also shows the behavior of the solar follower on a cloudy and rainy day where diffuse radiation prevails, showing that even in these conditions there is gain in the generation of the module with Tracer.